Employee incentives : impact of demographic differences & economic climates on the motivational effectiveness of monetary & non-monetary incentives on white-collar employees in Singapore. - Loh, Ming Choo. (2008)
This research investigates Singapore white collar employees' preferences for monetary and non-monetary incentives according to their varying demographic characteristics and under different economic conditions. We also investigate the impact of such preferences on the employees' motivation.